Biodentine as a Perforative Repair Material- A Review - Niha Naveed1 , Kishorekumar S2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Perforations are anomalous communications between the root canal system and the external dental surfacethat connects the pulp cavity to the periodontal tissue. Current advances in biomaterials has made the recoveryof tooth structure and function possible even in the most complicated cases. Ideally, perforations should beimmediately repaired with a biocompatible material to seal the communication between the perforation siteand the gingival sulcus in order to achieve a more favorable prognosis. This review article is focussed onBiodentine as perforative repair material, and has found to provide good biocompatibility, bioactivity, highcompressive strength and a short setting time.